Propuesta didáctica de juegos de exploración y experimentación como estrategia didáctica de desarrollo de funciones básicas en la escuela Dr. José María Velasco Ibarra en la parroquia Ignacio Flores del cantón Latacunga, provincia de Cotopaxi durante el periodo 2012-2013 - Arellano Iza, Elvia Paola (2015)
This work investigative work is the result of an exhaustive investigation, with regard to the educational help to the development at the early child of the first year of basic education at "Dr. Jose Maria Velasco Ibarra "School.in the parish Ignacio Flores. That allow the development of the basic functions as (laterality, perception and visual discrimination, perception and auditory discrimination, fine motor, and gross, corporal scheme, temporary and spatial orientation, static and dynamic balance, and rhythm)To improve the didactic strategies in the school before mentioned, that will be usefulness to satisfy the needs and worries of all those that could help to give a feasible solution for the development of the infant for which was taken account the use of different technologies and research that were used as a tool with which the summary of information was feasible across the empirical method, statistical method and observation for what it gets to the conclusion that the direct beneficiaries of this investigation are the teachers, parents and specially the children will contribute to their physical and intellectual development that in a future they do not have problems inside the learning for which one has seen necessary to realize a didactic proposal like: games exploration and experimentation.